THE Pemanfaatan Daun Kopi (Kawa Daun) Sebagai Penurun Tekanan Darah Tinggi pada Akseptor KB Suntik: UTILIZATION OF COFFEE LEAVES (KAWA LEAVES) AS A REDUCTION OF HIGH BLOOD PRESSURE IN INJECTING KB ACCEPTORS - Ustifina Hasanah Hsb; Herviza Wulandary Pane (Jurnal Kesehatan Komunitas, 2020)
The percentage of hypertension sufferers wherein women who have a higher hypertension rate is 28.8%, it occurs because it is influenced by the rate of contraceptive use, where the prevalence rate of contraceptive use tends to increase in 1991 - 2012 by 50% to 62%. The purpose of research to know the content in the decoction of coffee leaves and to know the effect of coffee leaf stew on the decrease in high blood pressure levels in the contraceptive injection aceptor. This research was a pre-experimental study with pre-test and post-test design and used Complete Random Design (RAL). Then tested to a sample of women with contraceptive injection as many as 60 people, the technique before drinking the boiled water of coffee leaves, the mother in the tension first to know how much change after drinking boiling water coffee leaves. The results of the study in the decoction of coffee leaves there are tannin levels, flavonoid levels that increase antioxidants that are very needed in hypertension sufferers. Majority of blood pressure respondents before consuming coffee leaf stew having stage 1 hypertension as many as 20 people (60.0%), then pre-hypertension amount 25 people and hypertension stage 2 in every 15 people (20,0%). Blood pressure of respondents after consuming pandan leaf stew the majority of the respondent's blood pressure decreased and became pre-hypertension as many as 25 people (41.0%), hypertension stage 1 20 (34%), hypertension stage 2 as many as 15 people (25%). It can be concluded the decoction of coffee leaves is very beneficial for a decrease in the high blood pressure of contraceptive injection acceptor.